2018
DOI: 10.1159/000495313
|View full text |Cite
|
Sign up to set email alerts
|

Is There A Relation Between Serum Uric Acid Values and Prostatic Calculi Presence?

Abstract: Objective: We planned to examine the connection between serum uric acid (UA) values and prostatic calculi (PCal) presence and to evaluate the relation between PCal and other etiological factors. Methods: Patients between 20 and 60 years of age who were referred to the clinic with any reason and had non-contrast abdominal tomography (NCACT) for PCal were included in the study. While the patients were separated into 2 groups based on their serum UA level as ≥7 mg/dL (Group 1) and < 7 mg/dL (Group 2), NCACT was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Balasar et al. (2019) found that high UA was significantly associated with prostatic calculi, but serum UA was not related to PSA levels. Another study in China was proved the relationship of uric acid and prostatic calculi.…”
Section: Discussionmentioning
confidence: 99%
“…Balasar et al. (2019) found that high UA was significantly associated with prostatic calculi, but serum UA was not related to PSA levels. Another study in China was proved the relationship of uric acid and prostatic calculi.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al reported that age and the anteroposterior diameter of the prostate were stronger risk factors for PC than other factors, with bilirubin level being the only protective factor found in the study after adjustment for other factors (5). Moreover, metabolic disorders could contribute to the formation of PC, and serum uric acid might participate in the formation of PC (18)(19)(20)(21). Moreover, Qian et al speculated that patients with PC often seek medical consultation due to psychological or emotional reasons, and thus experience a decreased frequency of sexual activity with increasing depression, which ultimately leads to the excretion of prostatic secretions that are involved in the formation of PC (22).…”
Section: Formation Of Pcmentioning
confidence: 99%